Stress, Anxiety, and Depression during Sudan War 2024 “A study of Displaced People in Shelter Centers in Al- Gazeera and Sinnar State” - Sabon , Manal Al-Tayeb (Dirasat: Educational Sciences, 2024)
Objectives: This study aimed to measure the level of psychological stress, depression, and anxiety among displaced people during the Sudan war in 2024. Methods: the study used a descriptive approach, through using Arabic version of DASS-21 scale, and primary data form. The study sample consisted of (511) displaced persons in shelter centers in states of Al-Jazira and Sinnar, were selected by random stratified method. Results: study showed that level of depression among the displaced during 2024 Sudan War was high, psychological stress was moderate, and anxiety was low. There was a relationship between depression, psychological stress, and anxiety among the displaced, and there were no differences in level of depression and psychological stress between those exposed to looting and those not, and the presence of differences in anxiety, in favor of those exposed to looting. The study also found differences in the level of anxiety and psychological stress between those exposed to rape and those not subjected to rape, in favor of those exposed to rape, and that there were no differences in level of depression depending on the variable of exposure to rape, and no differences in the level of depression, psychological stress and anxiety between those exposed to physical injuries and those not. Conclusion: study recommends the need to provide counseling and treatment programs for displaced people in shelter centers to alleviate psychological pressure, anxiety, and depression, which leads to improving their mental health.